2023
DOI: 10.3390/v15020315
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Porcine Adeno-Associated Virus Capsid Protein with Nuclear Trafficking Protein Importin Alpha Reveals a Bipartite Nuclear Localization Signal

Abstract: Adeno-associated viruses (AAV) are important vectors for gene therapy, and accordingly, many aspects of their cell transduction pathway have been well characterized. However, the specific mechanisms that AAV virions use to enter the host nucleus remain largely unresolved. We therefore aimed to reveal the interactions between the AAV Cap protein and the nuclear transport protein importin alpha (IMPα) at an atomic resolution. Herein we expanded upon our earlier research into the Cap nuclear localization signal (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 70 publications
5
10
0
Order By: Relevance
“…4B). This is consistent with recent studies demonstrating that porcine adeno-associated virus capsid protein possesses a bipartite NLS with a 26 aa linker (52), and that distantly located NLSs in SOX2 make a contiguous interface with IMPa3 (53). Furthermore, all tested HPyV LTA cNLSs exhibited a certain specificity with respect to IMPa isoforms, with those from WUPyV and JCPyV binding preferentially to IMPa1, and that from KIPyV binding preferentially to IMPa7.…”
Section: Conservation Of Cnlss Among All Known Pyv Ltas 95% Of Ltas F...supporting
confidence: 91%
See 1 more Smart Citation
“…4B). This is consistent with recent studies demonstrating that porcine adeno-associated virus capsid protein possesses a bipartite NLS with a 26 aa linker (52), and that distantly located NLSs in SOX2 make a contiguous interface with IMPa3 (53). Furthermore, all tested HPyV LTA cNLSs exhibited a certain specificity with respect to IMPa isoforms, with those from WUPyV and JCPyV binding preferentially to IMPa1, and that from KIPyV binding preferentially to IMPa7.…”
Section: Conservation Of Cnlss Among All Known Pyv Ltas 95% Of Ltas F...supporting
confidence: 91%
“…4), in accordance with the notion that efficiency of nuclear transport depends on IMPα:NLS binding affinity (10,24). HPyV LTA bipartite cNLSs bound IMPa with higher affinity compared to monopartite cNLSs (Table VII), as was expected from biochemical data from a range of laboratories demonstrating that bipartite NLSs bind to IMPa with higher affinity than monopartite NLSs (11,52). Spacing between the basic aa stretches, known as the linker region, is also variable, ranging from 11 aas for MWPyV LTA to 32 aas for HPyV12 LTA (Fig.…”
Section: Conservation Of Cnlss Among All Known Pyv Ltas 95% Of Ltas F...supporting
confidence: 85%
“…functional variability in the nuclear targeting activity of the HPyV LTA cNLSs described here is likely the consequence of differences in IMPα binding properties, as observed in EMSA and FP experiments (Figure 5, Figure S4), consistent with the notion that nuclear transport efficiency depends on IMPα:cNLS binding affinity (Hodel et al, 2006;Smith et al, 2018). HPyV LTA bipartite cNLSs bound IMP αΔIBB with higher affinity compared to monopartite cNLSs (Table S6), as was expected from what has previously been shown in the literature (Hoad et al, 2023;Hodel et al, 2001). Spacing between the basic aa stretches, known as the linker region, is also variable, ranging from 11 aas for MWPyV LTA to 32 aas for HPyV12 LTA (Figure 4A).…”
Section: Binding Properties Of Hpyv Lta Cnlss With Impα Isoformssupporting
confidence: 89%
“…The structural evidence presented here provides insight into the mechanisms involved in AAV and importin interactions, and intriguingly describes a bipartite NLS utilizing regions of the N-terminal domain outside of those revealed in earlier studies [43, 45]; comprising residues found in both VP1 and VP2 Cap isoforms. EMSA and FP data further solidified this evidence and showed that there is a clear difference in binding affinities of AAV 09YN capsid protein with importin isoforms ().…”
Section: Discussionmentioning
confidence: 63%
“…Once the cargo:IMPα:IMPβ, or cargo:IMPβ complex has travelled through the nuclear pore, Ran-GTP dissociates the complex and IMPα and IMPβ proteins are recycled back into the cell cytoplasm to continue facilitating the nuclear import of cargo proteins [40,41]. It has been shown [42][43][44][45] that AAV capsid proteins can interact with host importin proteins to enter the nucleus.…”
Section: Introductionmentioning
confidence: 99%